Determinan Kejadian Komplikasi Persalinan di Indonesia (Analisis Data Survei Demografi dan Kesehatan Indonesia Tahun 2017) - Hulwatullaini, Hulwatullaini; Rosidati, Catur (Journal of Religion and Public Health, 2023)
AbstractDelivery complictions are conditions that can harm health on mother and her infant in delivery. The purpose of this study was to determine the factors that most influence the delivery complications in Indonesia. This study used the Indonesian Demographic and Health Survey (IDHS) data in 2017. The research design used was a cross sectional design. The data analysis used was a multivariate logistic regression prediction model. The number of samples was 13,261 mothers who had given birth with the last birth occurred in the five years preceding the survey.The results showed nine variables were determinants of delivery complication. The most determinant factor affecting delivery complications was the pregnancy complications with an odds ratio of 1,742 (95% CI 1,519-1,999). For this reason, it is necessary to collaborated with various parties and strengthen policies in an effort to detect high risk pregnancies to prevent delivery complications.Keywords: Complications, Delivery, Determinants of Islam